2014
DOI: 10.1002/2014ja020614
|View full text |Cite
|
Sign up to set email alerts
|

Statistical investigation of Kelvin‐Helmholtz waves at the magnetopause of Mercury

Abstract: A large study of Kelvin-Helmholtz (KH) waves at the magnetopause of Mercury covering 907 days of data from the MErcury Surface Space ENvironment GEochemistry Ranging spacecraft have resulted in 146 encounters of not only nonlinear KH waves but also linear surface waves, including the first observations of KH waves at the dawnside magnetopause. Most of the waves are in the nonlinear phase (90%) occur at the duskside magnetopause (93%), under northward magnetosheath magnetic field conditions (89%) and during gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 33 publications
5
73
0
Order By: Relevance
“…The large majority of KHWs observed in Liljeblad et al (2014) were identified at the duskside magnetopause. As shown by Liljeblad et al (2015), MESSENGER covers the Hermean magnetosphere almost symmetrically during the year 2011.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The large majority of KHWs observed in Liljeblad et al (2014) were identified at the duskside magnetopause. As shown by Liljeblad et al (2015), MESSENGER covers the Hermean magnetosphere almost symmetrically during the year 2011.…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps these dawnside KHWs do indeed frequently develop at the magnetopause but are constantly repressed by certain conditions of the surrounding environment (such as a broader velocity shear layer or a low-latitude boundary layer present most often at the dawnside as reported in Liljeblad et al (2015)) and will therefore not be as clearly visible as the duskside KHWs. Thus, they are more difficult to identify with the criteria used in Liljeblad et al (2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These orbits also passed through Mercury's dusk magnetopause. Analogous data from orbits passing through Mercury's dawn magnetopause, also examined, were not used in this analysis because of the absence of abundant Na + or frequent evidence for K‐H vortices [ Raines et al ., ; Liljeblad et al ., ]. Instead, we focus on the differences between the dayside and nightside of the dusk terminator, where there is a strong spatial gradient in Na + content.…”
Section: Data Selection and Analysismentioning
confidence: 99%
“…Many large‐scale structures of the magnetosphere have been successfully reproduced by global simulations using both magnetohydrodynamic (MHD) [ Kabin et al ., ; Benna et al ., ] and hybrid techniques [ Wang et al ., ; Trávníček et al ., ; Schriver et al ., ]. Some features, such as the preferential formation of Kelvin‐Helmholtz (K‐H) vortices along Mercury's duskside magnetopause (MP) [ Boardsen et al ., ; Sundberg et al ., ], with a few also observed on the dawnside MP [ Liljeblad et al ., ] (Figure ), have been linked to kinetic scale plasma physics [ Nakamura et al ., ; Paral and Rankin , ]. These large‐scale (comparable to a Mercury radius, R M , or 2440 km) K‐H vortices may be capable of transporting substantial quantities of mass and energy between the solar wind and Mercury's magnetosphere, as has been observed at other planetary systems [e.g., Lee et al ., ; Hasegawa et al ., ; Masters et al ., ; Wilson et al ., ; Delamere et al ., ].…”
Section: Introductionmentioning
confidence: 99%